Use of Bacillus pretiosus and Pseudomonas agronomica for the Synthesis of a Valorized Water Waste Treatment Plant Waste as a Biofertilizer Intended for Quercus pyrenaica L. Fertigation - Diana Penalba-Iglesias; Marina Robas-Mora; Daniel González-Reguero; Vanesa M. Fernández-Pastrana; Agustín Probanza; Pedro A. Jiménez-Gómez (Biology)
The loss of hectares of forest areas has become a global issue that has worsened over recent years due to unsustainable human activities. In a context of limited availability of productive land, it is urgent to adopt efficient strategies to recover the affected natural areas. Actions based on a circular economy, such as the use of organic chemical matrices recovered from water waste treatment plant waste, have proven to be effective. In this regard, the addition of plant growth-promoting bacteria (PGPB), such as Bacillus pretiosus and Pseudomonas agronomica, can contribute to the chemical treatment, favoring the recovery of soils, accelerating the recovery of vegetation cover, and inducing an increase in biodiversity. In this research, the effect of bio-fertigation under controlled laboratory conditions in Quercus pyrenaica is evaluated. After a thirty-six-week trial, the biometric and nutritional parameters of the plants were harvested and measured, and the diversity and composition of the metagenomes of their rhizospheres were evaluated. As well, the cenoantibiogram and the metabolic diversity were measured. The results showed that the use of these biofertilizers increased the variables related to plant production, quality of plant composition as an indirect means of their resilience, as well as an increase in rhizospheric microbial diversity and a reduction in their MIC resistance to the most widely used antibiotics. For all these reasons, the use of the biofertilizer result of the combination of WWTP waste, Bacillus pretiosus, and Pseudomonas agronomica is postulated as an environmentally friendly strategy that can contribute to the recovery of potential oak forest areas.